THE RELATIONSHIP BETWEEN THE EFFECTIVENESS OF "INGENIOUS" BEHAVIOR IN EFFORTS TO CONTROL HYPERTENSION AT PRODUCTIVE AGE IN THE WORKING AREA OF THE JOMBANG HEALTH CENTER IN CILEGON CITY IN 2023 - Yanzela Putri Azis; Ikhlasiah, Marthia; Ismarina (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to evaluate the relationship between the effectiveness of "CERDIK" behavior (Health Check, Get Rid of Cigarette Smoke, Diligent Physical Activity, Balanced Diet, Get Enough Rest, and Manage Stress) in efforts to control hypertension in productive age in the Jombang Health Center Working Area of Cilegon City in 2023. The study used quantitative methods with descriptive, analytical and cross-sectional design types of research. The study population involved hypertensive patients of productive age recorded in the working area of the Jombang Health Center, Cilegon, with a total of 30 patients. Data collection was conducted through interviews and questionnaire filling. The p values of the independent t-test are 0.000, 0.000, 0.000, and 0.000, respectively for Education, Knowledge, Family Support, Eliminating Cigarette Smoke and Diligent Physical Activity. The results of statistical analysis show a relationship between these variables in respondents' behavior with hypertension control at productive age. There were significant differences in diastolic and systolic blood pressure between the group that underwent the "CERDIK" behavior and the group that did not. The group that adopted the "DODGY" behavior had lower blood pressure. The conclusion of this study is that "SMART" behavior has an important role in controlling hypertension in productive age. Therefore, health education resources and efforts need to be increased, especially in groups with less education, to increase awareness and application of "SMART" behaviors. This research contributes to understanding the importance of healthy behavior in controlling hypertension in productive age. The increasing prevalence of hypertension in Indonesia and its significant impact shows the urgency of increasing health awareness and education in the community.